Mental Disiplin di Era Disruptif - Khamam Khosiin (CV. Syntax Corporation Indonesia, 2022)
The development of technology and information in the 4.0 era is accelerating. One of the impacts is that humans move faster, are adaptable and have creative spirits at work. In the midst of this global competition, a creative attitude and mentality is the main key to getting through it. However, not all humans are able to get through it. This research aims to find out how the mentality that must be formed in this modern era, its relevance to the Qur'an, and its actualization in everyday life. The research uses qualitative methods with the concept of mental discipline in the disruptive era with stages of knowledge about: 1) The role of disruptive era actors. 2) Mental revolution. The results of this study are that there are two stages to form a creative mentality, namely the first stage is personal self. the second stage is to observe the surrounding environment and develop the potentials that exist in the environment.